Tubular Carcinoma of the Breast: Advantages and Limitations of Breast Tomosynthesis - Filipa Vilaverde; Ana Rocha; Alcinda Reis (Case Reports in Radiology)
Tubular carcinoma of the breast is a rare variant of invasive ductal carcinoma. We report a case of 42-year-old asymptomatic female with a histopathological proven multifocal tubular carcinoma, studied by mammography, Tomosynthesis, Ultrasound, and Magnetic Resonance. Herein, we discuss the advantages and limitations of Tomosynthesis, an emerging imaging technique, in this particular case.